Intercultural Disagreement: Implementing the Right to Prior Consultation in Peru. (September 2019) - Ilizarbe, Carmen
How do state and indigenous representatives process disagreement? What challenges does cultural difference pose to intercultural dialogue? An analysis of the debates that preceded the implementation of the right to prior consultation of indigenous peoples in Peru points to the normative orientation toward consensus that informs the design of processes of intercultural dialogue and concludes that the structure and foundations of disagreement must be taken into account for fair, democratic dialogue to exist. ¿Cómo procesan el desacuerdo los representantes estatales e indígenas? ¿Qué retos plantea la diferencia cultural al diálogo intercultural? Un análisis de los debates que precedieron la implementación del derecho a la consulta previa de los pueblos indígenas en Perú apunta a la orientación normativa hacia el consenso que informa el diseño de los procesos de diálogo intercultural y concluye que la estructura y los fundamentos del desacuerdo deben tomarse en cuenta para que exista un diálogo justo y democrático.